The theological turn of postmodernity: to be alive again - Idziak-Smoczynska, Urszula (Approaching religion, 2013)
This article discusses the role of religion in the philosophy of Jacques Derrida. The author considers a specifically Christian, affirmative character of deconstruction that is found through the biblical references of Derrida, inspired by his forgotten master Gérard Granel. This line of argument opposes both the presence of Heideggerian death drive in Derrida’s subject and advances the possibility of a genuinely Christian rebellious subject as an answer to the question; who comes after the subject? Derrida’s thought informs us about the affective and weak concept of subjectivity that might be fruitful for the development of new outlines for the social realm of subjectivity.